Загрози використання штучного інтелекту на малопотужних процесорах для організації акустичного каналу витоку - Передерій, І. А. (ХНУРЕ, 2024)
Artificial intelligence (AI) has emerged as a powerful ally in the ongoing battle against cybersecurity threats. With the proliferation of connected devices and the Internet of Things (IoT), the need for robust and adaptive security solutions has never been more pressing. This article explores the convergence of AI and low-power processors in fortifying cybersecurity defenses, presenting both opportunities and challenges in this rapidly evolving landscape
Keywords: малопотужний процесорах; акустичний канал витоку